The Development of English Vocabulary Teaching Material Through Cooperative Learning for Grade Vii Students of Smps Langkat Binjai 2025/2026 - Farhan, Arif; Asnawi; Harianto II; Risnawaty (International Journal of Educational Research Excellence (IJERE), 2026)
Guided by the research questions, this study is designed to achieve three main objectives. To design and develop a prototype of English vocabulary teaching materials based on Cooperative Learning principles for Grade VII students at SMP Langkat Binjai. To validate the developed materials through expert evaluation and pilot implementation. To assess the effectiveness of the materials in enhancing students’ vocabulary acquisition and active learning participation. This research employs a Research and Development (R&D) approach with the ADDIE model as its instructional design framework. R&D is appropriate for studies that aim to produce educational products—such as teaching materials-and systematically test their quality and effectiveness in real-world contexts. The ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was selected due to its structured yet flexible nature and its wide acceptance in educational material development. The conclusions of this research can be categorized into five major areas corresponding to the ADDIE model: Development of Materials, Validation of Materials, Implementation of Materials, Effectiveness of Materials, Practicality and Pedagogical Implications